E-Government 2.0 Engagement Model Based on Social Media Patterns for Supporting Public Service Delivery Transformation (PSDT) Programme (S/O: 13259) - Mohd Nadzir, Maslinda; Othman, Nafishah; Kamaruddin, Siti Sakira (UUM, 2018)
Social media is a platform widely used by users to connect and form online communities to socialize and share information. Social media use in government agencies has the potential to promote a positive perception towards the government agencies. It makes the government agencies more reachable to the citizens, while offering the citizens opportunities to become actively engaged with the government agencies. However, there is lack of social media usage in some of the government agencies in engaging and disseminating information to the citizens. This study investigated several Malaysian government agencies’ Facebook pages by carrying out a qualitative content analysis on the page posts and citizens’ feedback to identify the extent of social media usage to encourage citizen engagement. The analysis result revealed that most government agencies posts information related to public awareness in their Facebook page while most citizen feedbacks are through the number of ‘likes’ on the posts regarding promotions. However, there is a lack of feedback from the citizens in terms of shared posts. Then, an e-government 2.0 engagement model based on Facebook engagement patterns has been identified in this study. This model includes five types of information posted by government agencies through its Facebook pages and three Facebook engagement indicator which are ‘likes’, ‘shares’ and ‘comments’. The findings of this study are beneficial to government agencies to improve the visibility of their Facebook pages with the aim of improving the engagement strategy between them and the citizens